2016
DOI: 10.3892/ol.2016.4696
|View full text |Cite
|
Sign up to set email alerts
|

Harmine combined with paclitaxel inhibits tumor proliferation and induces apoptosis through down-regulation of cyclooxygenase-2 expression in gastric cancer

Abstract: Abstract. Cyclooxygenase-2 (COX-2) serves an important role in the carcinogenesis and progression of gastric cancer. Harmine (HM) and paclitaxel (PTX) are reported as promising drug candidates for cancer therapy, but whether a synergistic anti-tumor effect of HM combined with PTX exists in human gastric cancer remains unknown. The present study evaluated the effects of HM and/or PTX on cell proliferation and apoptosis in a gastric cancer cell line, SGC-7901. HM and PTX inhibited cell proliferation in a dose-de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…Many anticancer drugs function by inducing apoptosis. 1 , 2 Paclitaxel induces apoptosis in different cancer cells, including breast cancer, 23 gastric cancer, 43 colon cancer, 44 and leukemia cells 45 by modifying mitochondrial transition permeability, activating caspase-8 and caspase-3, 44 , 46 and Bcl-2 inactivation by a mechanism that may involve the binding of paclitaxel to this antiapoptotic protein. 47 As demonstrated in this study, heat-killed baker’s yeast also acts as an anticancer agent via induction of apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Many anticancer drugs function by inducing apoptosis. 1 , 2 Paclitaxel induces apoptosis in different cancer cells, including breast cancer, 23 gastric cancer, 43 colon cancer, 44 and leukemia cells 45 by modifying mitochondrial transition permeability, activating caspase-8 and caspase-3, 44 , 46 and Bcl-2 inactivation by a mechanism that may involve the binding of paclitaxel to this antiapoptotic protein. 47 As demonstrated in this study, heat-killed baker’s yeast also acts as an anticancer agent via induction of apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…The anticancer activity of harmine in human cancers has been evidenced. Harmine induces proliferation inhibition, apoptosis and pro-death autophagy in gastric cells, and shows synergistic effects with paclitaxel [57,58]. However, the efficiency, sensitivity and specificity of these compounds in the 10 NSCLC patients should be further validated in clinical practices.…”
Section: Discussionmentioning
confidence: 99%
“…The top two inhibitory compounds were "harmine," a drug for Parkinson's disease, and "chrysin," an antifungal drug. A search of the literature showed that harmine induces the apoptosis of gastric cancer cells by down-regulating cyclooxygenase-2 (COX-2) expression (Yu et al, 2016) and that chrysin inhibits COX-2 expression in macrophages and induces Akt inactivation in U937 cells (Woo, Jeong, Inoue, Park, & Kwon, 2005). Thus, COX-2 is a common target of harmine and chrysin.…”
Section: Cyclooxygenase-2 Is Essential For the Apical Extrusion Of mentioning
confidence: 99%